Manajemen Tata Usaha Dalam Peningkatan Kualitas Pelayanan Administrasi: Di SMA Negeri 1 Dukun - Cici Rumi Mulyani Rumi; Qomaruddin; Nur Fatih Ahmad (Program Pascasarjana Pendidikan Islam Universitas Islam Darul Ulum Lamongan, 2026)
This article aims to analyze the ontology and epistemology of revelation in the Qur'an through a critical study of classical and contemporary theological thought while integrating it with modern socio-religious perspectives. The research focuses on how revelation is understood as a source of absolute divine authority as well as an object of rational inquiry within the Islamic intellectual tradition. The study begins with the epistemological tension between the normative-theological approach, which emphasizes the sacredness of the text, and the academic-contextual approach that situates revelation within historical and social frameworks. In the era of globalization and digital transformation, shifts in religious authority and the emergence of new interpretive discourses make this discussion increasingly relevant for reaffirming the role of revelation in the lives of contemporary Muslims. This study employs a library research method by combining theological, philosophical, and sociological analyses. The primary data sources include works of classical and contemporary Muslim thinkers and literature related to the living Qur’an studies. The findings indicate that ontologically revelation continues to be understood as a transcendent divine kalam, while epistemologically it remains open to rational and contextual approaches without losing its sacred authority. The integration of revelation and reason reflects the dynamic nature of Islamic intellectual tradition that remains adaptive to social change. The study concludes by emphasizing the importance of a multidimensional approach in the study of revelation and recommends the development of integrative Islamic education.